Impact of Managerial Perception of Intellectual Capital Disclosure Practices on the Credibility of the Financial Statements - Jayasooriya, S.D.; Gunawardana, K.D.; Weerakoon Banda, Y.K. (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2019)
This study aims to investigate the impact of managerial perception of intellectual capital disclosure practices on the credibility of the financial statements. As the method, the primary data was collected through a questionnaire. The targeted sample was the financial managers who are directly involved in preparing financial statements in the public limited companies. 150 questionnaires were distributed covering the financial managers in all the sectors using the stratified random sampling method. There were three hypotheses developed covering the major components of intellectual capital as human, customer and social. Correlation analysis was conducted to test the hypothesis using the SPSS software. It was found that there is a relationship between the managerial perception of intellectual capital disclosure practices and the credibility of the financial statements. Through a regression analysis, it showed that there is an impact of intellectual capital disclosure practices on the credibility of financial statements. The managers believe that the existing reporting practices do not represent the reality of the organizational performance until the intellectual capital is incorporated to the financial statements. Further, they have suggested that there should be a proper mechanism to report the intellectual capital in the financial statements or in the annual reports to avoid such kind of misrepresentation.
Keywords: Intellectual Capital, Disclosure Practices, Credibility, Financial Statements